Multidisciplinary Respiratory Medicine - Sanguinetti, Claudio Maria; Blasi, Francesco; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Multidisciplinary Respiratory Medicine is the official journal of the Italian Respiratory Society - Società Italiana di Pneumologia (IRS/SIP). The journal publishes on all aspects of respiratory medicine and related fields, with a particular focus on interdisciplinary and translational research. The interdisciplinary nature of the journal provides a unique opportunity for researchers, clinicians and healthcare professionals across specialties to collaborate and exchange information. The journal provides a high visibility platform for the publication and dissemination of top quality original scientific articles, reviews and important position papers documenting clinical and experimental advances. Given the journal s interdisciplinary character, the target readership is wider than respiratory medicine, embracing numerous related disciplines (allergology, immunology, internal medicine, geriatrics, infectious diseases, intensive care, etc) and health professionals.
Keywords: Medicine; Critical care medicine; Respiratory organs -- Diseases; Thoracic surgery; Medicine & Public Health; Pneumology/Respiratory System; Intensive / Critical Care Medicine; Thoracic Surgery